1985
DOI: 10.1159/000118195
|View full text |Cite
|
Sign up to set email alerts
|

Tiapride: Effects on Tardive Dyskinesia and on Prolactin Plasma Concentrations

Abstract: In a placebo-controlled double-blind crossover study of 21 patients chronically treated with neuroleptics and suffering from tardive dyskinesia, tiapride (600 mg/day, mean plasma level: 682 ng/ml) exhibited a transient efficacy during 12 weeks of treatment, most distinct in the 6th week (p < 0.01). Tiapride induced an increase of prolactin plasma levels, on the average, from 1,195 to 2,179 µlU/ml (p < 0.01). Tiapride was well tolerated. Increase of parkinsonism was only mild and not significant. The results un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…However, the effect is said to decrease after a certain perlod of time. This has also been seen in a well documented and controlled study by Greil et al (1985) who demonstrated an effective treatment of tardive dyskinesia with a fixed dose of 600 mg/d, but observed a reduction of tiapride effects after 8 weeks of treatment. This was very likely due to the fixed dosis regimen used in Greils study.…”
Section: Indicationssupporting
confidence: 55%
“…However, the effect is said to decrease after a certain perlod of time. This has also been seen in a well documented and controlled study by Greil et al (1985) who demonstrated an effective treatment of tardive dyskinesia with a fixed dose of 600 mg/d, but observed a reduction of tiapride effects after 8 weeks of treatment. This was very likely due to the fixed dosis regimen used in Greils study.…”
Section: Indicationssupporting
confidence: 55%
“…Tiapride has been reported as effective in the treatment of levodopa induced involuntary movements (Lees et al 1979;Nielsen 1983), Parkinson's disease (Price et al 1978), tardive dyskinesia (Greil et al 1985) and in Huntington's disease (Lhermitte et al 1977;Buruma et al 1982;Roos et al 1982).…”
mentioning
confidence: 99%
“…The side effect persists after withdrawal, in some cases irreversibly. It is observed in about 20-30 %of patients treated chronically with the neuroleptic drugs (Greil et al, 1985) and its incidence increases with the age of the patients: Age seems the most important risk factor with regard to this side effect (Haag 1985). The most characteristic signs of tardive dyskinesia are stereotyped involuntary movements of the lips, rapid protrusions of the tongue and lateral jaw movements, sometimes choreiform movements of the extremities or slower, dystonie movements and postures of neck, extremities and trunk.…”
Section: Prevalence and Phenomenology Of Extrapyramidal-motor Släe Efmentioning
confidence: 99%